(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article defines features of language репрезентации a mental condition «despair»; explains specificity of phraseological units with nonverbal component in a role of the semantic indicator is defined, the place of such steady expressions in system of those means which form an emotional code of language.